Black Subjects : Identity Formation in the Contemporary Narrative of Slavery - Keizer, Arlene (Cornell University Press, 2018)
Writers as diverse as Carolivia Herron, Charles Johnson, Paule Marshall, Toni Morrison, and Derek Walcott have addressed the history of slavery in their literary works. In this groundbreaking new book, Arlene R. Keizer contends that these writers theorize the nature and formation of the black subject and engage established theories of subjectivity in their fiction and drama by using slave characters and the condition of slavery as focal points.In this book, Keizer examines theories derived from fictional works in light of more established theories of subject formation, such as psychoanalysis, Althusserian interpellation, performance theory, and theories about the formation of postmodern subjects under late capitalism. Black Subjects shows how African American and Caribbean writers' theories of identity formation, which arise from the varieties of black experience re-imagined in fiction, force a reconsideration of the conceptual bases of established theories of subjectivity. The striking connections Keizer draws between these two bodies of theory contribute significantly to African American and Caribbean Studies, literary theory, and critical race and ethnic studies.